Langages structurés et lien social - Alain Vaucelle; Henri Hudrisier (Tic & Société, 2010)
In this article, the authors propose a critical approach to interactivity through the use of markup languages and application frameworks. For twenty years, these languages have been reorganizing how interactivity is laid out in the development of information and communication technologies. Setters of standards, authors, users are organized into colleges of  governance in order  to design the evolution of these languages. This socialization is one of the essential levers of development of communicating systems.